The role of self in teacher development - Lipka, Richard P.; Brinthaupt, Thomas M., 1958- (SUNY series, studying the self., 1999)
"The Role of Self in Teacher Development explores some of the major transition points in becoming a teacher and focuses explicitly on how issues of self and identity bear on these different points. The contributors examine not only pre-service teachers, but also the first years of teaching, the characteristics of the master teacher, and the processes of reexamining and affirming one's identity as a teacher. A recurrent theme throughout the book is the importance of balancing the personal development of teachers with their professional development."--Jacket